Beberapa Keterkaitan Antara Politik dan Bisnis - James R. Situmorang (Jurnal Administrasi Bisnis, 2009)
Politics and business may seem to exist separately. Businesses primarily focus onstrategies and policies to improve operations and increase the profitability of compa-nies. Politics, on the other hand, play in a different arena, delving into the creation ofpublic policies for the advancement of constituents and the country. However, uponclose examination of how politics and business truly work, a connection betweenboth becomes apparent. The two influence each other.Keywords: politics, business, politician, businessman, country, company, eco-nomics, macroeconomics, goods and service, lobby, political party